Dawn of a new system - Bhagwati. Jagdish (2013)
Suggests that the the leadership of proposed preferential trade agreements should be exhorted to make rules and manage dispute settlement in these regional arrangements in a way that reflects lessons learned at the multilateral level. Adds that rule making must not be exclusive to these fora and also must not excluse those that are not members of the regional arrangements on the pretext that the U.S. lobbies know what is best for everyone. Notes as well that bilateral or regional forums must allow the views of non-members who belong to the WTO to be heard.